PENGEMBANGAN ‘BOARDGAME SPOTLIGHT 9 KATA KUNCI MODERASI BERAGAMA’ SEBAGAI MEDIA PEMBELAJARAN DAN PENGUATAN KOMUNITAS PEMUDA LINTAS IMAN - Mariatul Asiah; Riza Saputra (LP2M Universitas Ibrahimy, 2026)
This Community Service (Pengabdian kepada Masyarakat) activity addresses the superficial understanding of religious moderation among an inter-faith youth community in South Kalimantan, where traditional dialogue methods proved rigid and ineffective for the deep internalisation of values. The project's main objective was to develop an innovative educational board game named